Immigrant Peers and Foreign Language Acquisition - Colin P. Green; Kristine Bekkeheien Haaland; Jon Marius Vaag Iversen (Institute of Labor Economics (IZA), 2022)
Immigrants change the school environment. A focus has been on negative spillovers on native students' educational attainment. Yet, exposure to immigrant peers has the potential for a wider range of effects. This paper examines effects on foreign language acquisition focusing on Norway. In Norway all students are taught, and are assessed, in English from an early age. We demonstrate that exposure to native English-speaking peers increase Norwegian students' English language skills. We provide evidence that these spillover effects likely occur outside of the classroom. They are solely present for English language skills and provide evidence of positive spillovers from immigrant diversity in schools that is missing from the existing literature. Our results have implications for the wider social effects of immigration and how foreign languages are taught in schools.
Keywords: J15; I21; 330; immigration; English language attainment; educational attainment